A Methodology for an FPGA Implementation of a Programmable Logic Controller to Control an Atomic Layer Deposition System. (6th May 2022) - Jamieson, Peter; Blank, Donald; Ghanem, Janelle; McGrew, Tyler; Corti, Giancarlo
Abstract : In this work, we present an industrial cold walled Atomic Layer Deposition (ALD) system, which can be controlled by either a traditional programmable logic controller (PLC) system or a field-programmable gate array (FPGA) prototyping board. This work presents an FPGA controlled system that takes ladder diagram (LD) control for a PLC and converts this control to Verilog HDL and programs an FPGA such that the FPGA prototyping board is used to control a real industrial application. We explore this approach since FPGA implementation of LD control could significantly reduce the cost of implementing these controllers with other potential advantages such as the improved granularity of timing control from milliseconds to nanoseconds, additional available pins for inputs and outputs far exceeding that of microprocessors, and lower power consumption for control. In this work, we provide details and descriptions of our industrial system (ALD), the LD control of this system and its implementation, our software flow to convert LDs to Verilog HDL, and our FPGA prototype board design to replace the existing electronic controller. We show how our LD-Verilog HDL converter in conjunction with FPGAs matches a PLC and demonstrate some of the benefits of using an FPGA.